2019
DOI: 10.1096/fj.201802474rr
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol targets TyrRS acetylation to protect against radiation‐induced damage

Abstract: Resveratrol (RSV) has broad prospective applications as a radiation protection drug, but its mechanism of action is not yet clear. Here, we found that 5 µM RSV can effectively reduce the cell death caused by irradiation. Irradiation leads to G2/M phase arrest in the cell cycle, whereas RSV treatment increases S‐phase cell cycle arrest, which is associated with sirtuin 1 (SIRT1) regulation. Meanwhile, RSV promotes DNA damage repair, mainly by accelerating the efficiency of homologous recombination repair. Under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Moreover, our discovery of TyrRS being a biologically significant and physiologically relevant target of RSV that facilitates the conversion of trans-RSV to cis-RSV suggests that the cis-isomer of RSV is also a major isomer that evokes protective stress response. Other recent studies have also confirmed the TyrRS-PARP1 signaling in mediating the protective effects of RSV [120,229,296,[432][433][434]. However, there are still critical gaps in our knowledge.…”
Section: Cisand Trans-rsv Have Opposite Effects On Tyrrs-regulated Pamentioning
confidence: 93%
“…Moreover, our discovery of TyrRS being a biologically significant and physiologically relevant target of RSV that facilitates the conversion of trans-RSV to cis-RSV suggests that the cis-isomer of RSV is also a major isomer that evokes protective stress response. Other recent studies have also confirmed the TyrRS-PARP1 signaling in mediating the protective effects of RSV [120,229,296,[432][433][434]. However, there are still critical gaps in our knowledge.…”
Section: Cisand Trans-rsv Have Opposite Effects On Tyrrs-regulated Pamentioning
confidence: 93%
“…In mice, administration of RES attenuates radiation-induced intestinal damage via activation of sirtuin-1 [ 135 ], supporting lymphocyte [ 136 ] and intestinal functions recovery [ 137 ]. Under oxidative stress, RES promotes tyrosyl-tRNA synthetase acetylation, regulates relevant signaling proteins, and reduces apoptosis and DNA damage [ 138 ]. Clinical studies on RES as a normal tissue protector and potential tumor sensitizer are limited [ 139 ], mainly because RES possesses unfavorable bioavailability and pharmacokinetic properties.…”
Section: Medical Countermeasuresmentioning
confidence: 99%
“…RSV also targets tyrosyl-tRNAsynthetase (TyrRS), involved in protein synthesis, and TyrRS is linked to the regulation of genes associated with HRR (Cao et al, 2017). RSV causes inactivation of TyrRS, its translocation to the nucleus and, therefore, inhibits HRR (Gao et al, 2019).…”
Section: Hdac/kdac Inhibitorsmentioning
confidence: 99%